Autonomous Reconstitution of Fractured Hybrid Perovskite Single Crystals (Adv. Mater. 19/2022). Issue 19 (12th May 2022) - Al‐Handawi, Marieh B.; Dushaq, Ghada; Commins, Patrick; Karothu, Durga Prasad; Rasras, Mahmoud; Catalano, Luca; Naumov, Panče
Abstract : Hybrid Organic–Inorganic Perovskites In article number 2109374, Luca Catalano, Panče Naumov, and co‐workers address the poor mechanical robustness of bulk hybrid organic–inorganic perovskite (HOIP) crystals by demonstrating that broken centimeter‐size single crystals of a typical HOIP, MAPbI3, can readily self‐repair under mild compressive forces at ambient temperature. The self‐healed crystals show an impressive recovery of their mechanical and optoelectronic properties.